ICESat‐2 Precision Orbit Determination. Issue 4 (23rd April 2021) - Thomas, T. C.; Luthcke, S. B.; Pennington, T. A.; Nicholas, J. B.; Rowlands, D. D.
Abstract: The ICESat‐2 Precision Orbit Determination (POD) system computes the precise position of the laser altimeter instrument in inertial space, a measurement necessary for accurate geolocation of individual photon surface returns. ICESat‐2 POD solutions are generated by the reduction of Global Positioning System (GPS) double‐difference carrier phase observable residuals with NASA Goddard Space Flight Center's GEODYN software. Independent satellite laser ranging (SLR) measurements are withheld from the POD solutions and used as an independent arbiter of POD performance. Measurement model updates in the form of estimated GPS antenna phase center and satellite laser ranging retro‐reflector tracking point offset vectors as well as a GPS antenna phase center variation map have led to significant improvement in POD performance. GPS residual analysis and orbit precision analysis show no significant anomalous temporal or geographic POD performance issues. The independent SLR residual analysis indicates that POD solutions have achieved a radial orbit accuracy just below 1.5 cm, thus exceeding the mission radial orbit accuracy requirement of 3.0 cm by more than a factor of 2. Future POD processing updates have been identified and will lead to even further improvements in POD performance. Key Points: ICESat‐2 surface return elevation accuracy depends directly on the performance and accuracy of precisely positioning the instrument ICESat‐2 mission Precision Orbit Determination (POD) requirement is 3.0 cm radial RMS over a 24‐h period ICESat‐2 POD performance is achieving a factor of 2 improvement over the mission requirement at 1.5 cm radial RMS